IMPLEMENTASI PENGAMANAN BASIS DATA PASSWORD LOGING DENGAN TEKNIK ENKRIPSI PADA POLDA BENGKULU - Wahyudi, Jusuf; Riyanto, Nugroho Ponco; Sapri, Sapri (UNIVED Press, 2012)
Bengkulu Police Directorate Reskrimsus using Visual Basic 6.0 programming language. The formulation of the problem is how to design a database encryption software that will help in logging application security and database programs. The purpose of this research is to create a security system logging application program by using encryption and security techniques encryption as a cryptographic security of course.The place and time of the research conducted at the Office of the Police Directorate Reskrimsus Bhayangkara Bengkulu is in the No. 2 City Road Begkulu. The method used in this study were interviews, observation, and literature. At this stage of encryption on logging applications using the programming language Visual Basic 6.0From the discussion, it can be concluded that in Bengkulu Police Directorate Reskrimsus evidence in the record necessary for logging in with the password encryption techniques so that not all personnel can open and change it.